PENGARUH BEBAN KERJA, KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA (DI SMKN 1 PUJON KABUPATEN MALANG) - Muhammad Masykur; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT                                          This study aims to describe and analyze the effectof work load organizational commitment, and work motivation to work teacher perfomance in vocational high school 1 Pujon malang district. The type of this study is experimental. This study is using primary and secondary data which is obtained from distrubuting a questionnare and interview. This study consists of 43 active teacher i vocational high school 1 Pujon Malang.This study is used descriptive quantitative method which contains validity, reliability, normality, multicoliearity test, heterocodasity, multiple linear analysis, f test, and t test.The result of this study shows that (1) simultaneously effect of work load, organizational commitment, and work motivation toward teacher perfomance in vocational high school 1 Pujon Malang district. (2) partially the work loan variable has significantly effect through teacher perfomance furthermare the organizatinal commitmen has significantly effect and work motivation has significantly effect through the teacher performance in vocational high school 1 pujon malang.Key word: work load, organizational commitment, work motivation and perfomanc